Penerapan Metode Orff dalam Meningkatkan Kemampuan Ritmis Peserta Didik Sekolah Dasar: Single Subject Research (SSR) - Tresna Lia Noer Juliani; Resa Respati (JURNAL ARMADA PENDIDIKAN, 2026)
Rhythmic ability is one of the important elements in music learning at the elementary school level, which includes the ability to follow the beat, maintain tempo, identify and imitate rhythmic patterns, as well as synchronize movement and rhythm. However, in practice, there are still students who experience difficulties in following beats and maintaining rhythmic stability during musical activities. This study aims to determine the improvement of elementary school students’ rhythmic abilities through the implementation of the Orff method. This study employed a Single Subject Research (SSR) method with an A-B-A design. The research subject consisted of one third-grade elementary school student who experienced rhythmic difficulties in musical activities. Data were collected through performance tests. The data were analyzed using descriptive statistics with visual graph analysis presented in graphical form. The results showed that there was an improvement in rhythmic ability after the intervention using the Orff method. In the initial baseline phase (A1), the subject’s average rhythmic ability was 56%. After the intervention phase (B), the rhythmic ability increased to 80.4%, and in the final baseline phase (A2), it further increased to 86.7%. These findings indicate that the Orff method can help improve the rhythmic abilities of elementary school students.